Early Education Matter: The Power Of Child-Parent Attachment Quality In Predicting Child’s Executive Function - Yuliana Mukti; Donny Hendrawan (Jurnal Ilmu Keluarga dan Konsumen, 2018)
Parental caregiving is a cornerstone of child's early education primarily their cognitive performance. A positive attachment quality has proven to contribute to the child's higher-order thinking process, supported by cool and hot executive function (EF) skills. However, previous studies still found inconsistencies, particularly of which cool and hot EF components are being affected. Moreover, the presence of mother and father figure in parenting enriched the finding of child EF, but studies about father's figure related to child attachment quality are still limited. This study was a preliminary study that aimed to investigate the relationship between child's attachment quality with both mother and father and child's cool and hot EF on preschoolers. Child's attachment quality was assessed using ASCT (Attachment Story Completion Task) and child's EF was measured using Executive Function Battery Test. All of the activities were videotaped. Partial correlation was used to investigate the relationship between child attachment quality and child EF while gender, age and child attachment with one of the attachment figure are controlled. The result found that controlling variables influence the correlation between child's attachment quality and EF skills. This study presented important finding to improve the quality of early education through ameliorating parent-child relationship.